Impact of Covid-19 on Troubleshooting Loans in Practice of Village Credit Institutions - I Nyoman Sujana; Hartini Saripan; Gautam Kumar Jha (Law Doctoral Community Service Journal, 2022)
This article analyzes the Impact of COVID19 on the Settlement of Non-performing Loans in the Practice of Village Credit Institutions. The focus of the study is on the dilemma faced by LPDs in Some Traditional Villages in Denpasar City in resolving non-performing loans in the era of the COVID19 pandemic. This problem is the focus of the study, because non-performing loans are a very frightening specter for communal financial institutions such as LPDs, even more so in the era of the COVID19 pandemic. If one takes legal action, it will certainly result in very dangerous for the survival of the LPD concerned. By using the method of providing professional services through discussions with LPD Management in Denpasar City Traditional Villages in resolving the impact of COVID19 on the settlement of non-performing loans in LPDs. Based on the results of interviews and discussions with LPD administrators throughout the city of Denpasar, it can be found that the LPD management in the era of the COVID19 pandemic in resolving non-performing loans is faced with a dilemma, namely on the one hand LPD has a special mission to help and encourage the economic development of traditional villages and improve the welfare of traditional village manners, but on the other hand, with the COVID19 pandemic, it turns out that credits channeled to fund borrowing customers (who are actually village manners themselves) have difficulty fulfilling their obligations to return credit installments as agreed in the credit agreement. In this position, the LPD Management is faced with between saving credit to maintain the health of the LPDâ€™s operations, or by executing a guarantee (guarantee) which will certainly create suffering for the Krama Desa Adat itself. In this activity, a solution has been provided so that the settlement of non-performing loans faced by LPDs during the COVID19 Pandemic Era is resolved through the Principles of Balinese Customary Law. â€œParas Paro, Gilik seguluk, Sarpaya ya sabayantakaâ€.